Assessing Second Language Listening Over the Past Twenty Years: A Review Within the Socio-Cognitive Framework - He, Lianzhen; Jiang, Ziyun (Frontiers in Psychology, 2020)
The assessment of second language (L2) listening has received much attention. To understand the state-of-the-art research on L2 listening assessment, a total of 87 studies published in 14 peer-reviewed journals and two research report series between 2001 and 2020 were reviewed, using the socio-cognitive framework for developing and validating listening tests proposed by Weir (2005). Thirteen research themes were identified in relation to the six components of the framework, including test-taker characteristics, cognitive validity, context validity, scoring validity, consequential validity, and criterion-related validity. Context validity was the most investigated component, covering three research themes, that is, task setting, linguistic demands (input and output), and speakers. Based on a detailed analysis of the 13 research themes, recommendations for future research in L2 listening assessment were given.